Faktor-Faktor yang Berhubungan dengan Pemilihan Layanan Homecare oleh Pasien di Praktik Dokter X Tahun 2025 - Stefanny Stefanny; Ria Efkelin; Ratu Chairunisa (Pusat riset dan Inovasi Nasional, 2025)
Homecare services are increasingly recognized as a preferred healthcare option because of their practicality, flexibility, and accessibility, especially for elderly patients and individuals with physical limitations who face difficulties in reaching health facilities. This study aims to examine the relationship between consumer, provider, sociocultural, and organizational factors with patients’ preferences in selecting homecare services. Employing a quantitative approach with a descriptive analytical design, data analysis was conducted using the chi-square test to determine the significance of each factor. The findings reveal that consumer-related aspects, such as personal needs, convenience, and trust (p = 0.005), along with sociocultural influences including social norms, cultural values, and family support (p < 0.001), have a significant relationship with patients’ choices of homecare services. In contrast, provider factors (p = 0.096) and organizational factors (p = 0.161) were found to have no significant impact on the decision-making process. These results suggest that patients’ decisions are primarily shaped by internal motivations and sociocultural environments rather than institutional or organizational elements. Thus, it is essential for healthcare providers to focus on understanding community needs, cultural practices, and patient expectations to ensure that the services offered are both relevant and acceptable. By integrating cultural sensitivity and consumer-oriented strategies, homecare services can become more effective, trusted, and widely utilized within the community.